2001
DOI: 10.1039/b008645m
|View full text |Cite
|
Sign up to set email alerts
|

Superparamagnetic behaviour of γ-Fe2O3 nanoparticles dispersed in a silica matrix

Abstract: The structural and magnetic properties of two nanocomposites, containing respectively 16.9 and Fe 2 O 3 ÈSiO 2 28.5 wt.% were investigated. The samples were synthetized by a solÈgel method, using ethylene glycol Fe 2 O 3 , as a solvent, and heating the gels gradually to 900 ¡C. The procedure allowed us to obtain c-Fe 2 O 3 nanoparticles homogeneously dispersed in the amorphous silica matrix. The particles have a narrow size distribution and mean sizes from 3 to 6 nm depending on the iron oxide content. The mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
59
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(66 citation statements)
references
References 9 publications
5
59
2
Order By: Relevance
“…On the other hand, Martinez et al reported high value of coercivity H C = 3000 Oe and a very low saturation magnetization M S = 5 emu/g in nanosized maghemite [64]. A recent paper by Han 37.8 emu/g, and coercivities of 810 Oe and 1180 Oe, respectively [67]. Nadeem et al prepared ultrafine maghemite nanoparticles with size of about 4 nm, high coercivity of 3008 Oe and low saturation magnetization [68].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…On the other hand, Martinez et al reported high value of coercivity H C = 3000 Oe and a very low saturation magnetization M S = 5 emu/g in nanosized maghemite [64]. A recent paper by Han 37.8 emu/g, and coercivities of 810 Oe and 1180 Oe, respectively [67]. Nadeem et al prepared ultrafine maghemite nanoparticles with size of about 4 nm, high coercivity of 3008 Oe and low saturation magnetization [68].…”
Section: Introductionmentioning
confidence: 94%
“…These magnetic properties arise both from the atoms which reside on the surface of the nanoparticles, and from the finite number of atoms in the nanoparticle crystalline core. It has been shown that particle size, morphology, defects, core-shell and dipolar interactions have a large influence on the magnetic properties of the samples [1,56,62,63,65,[67][68][69][70][71][72][73][74]. Moreover, the finite size and surface effects are usually masked by the presence of particle size distribution and by a magnetic interaction between the particles, and it is very difficult to distinguish the real contribution of finite size and surface effects on the magnetic properties.…”
Section: Introductionmentioning
confidence: 97%
“…[6,7] As the particle size is reduced, the surface becomes predominant, [8] which can induce dramatic changes in the magnetic properties. [8][9][10][11] As a consequence of the low coordination of surface atoms, a disordered magnetic shell with spin-glasslike behavior may surround the ferrimagnetic core. These effects are more effective when the structural disorder increases.…”
Section: Introductionmentioning
confidence: 99%
“…Several techniques have been developed for the synthesis of such particles, for example, co-precipitation, [1,9,[14][15][16][17][18][19] sol-gel methods, [11,[20][21][22] or pyrolysis. [9,[23][24][25][26] Recently, inorganic or organometallic precursors have proved their efficiency, at high temperature, in the synthesis of monodispersed maghemite nanoparticles (NPs) in the presence of a stabilizing agent, such as ligands or surfactants.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, although bi-magnetic core/shell structures composed of soft/soft materials have been shown to also have appealing applications (e.g., in biosensors, hyperthermia, microwave absorption and magnetic resonance imaging) [89,[315][316][317]], they will not be discussed in this review. Similarly, nanoparticles with surface anisotropy effects [318][319][320] will not be considered in this review, even if they could be viewed as a purely "magnetic" (i.e., not structural) soft/hard core/shell configurations.…”
Section: Static Magnetic Propertiesmentioning
confidence: 99%